O uso da biomassa da cana-de-açúcar para cogeração e produção de energia elétrica: análise termodinâmica, termoeconômica e econômica: estudo de caso - Santos, Rafael Delapria Dias dos (2014)
This work has accomplished thermodynamic, thermoeconomic and economical analyses of the cogeneration of an industrial power plant in a sugar-alcohol factory. Four situations are analyzed. In the first case, the factory produces electricity for its own consumption (its plant is already amortized). In the second case, which is considered hypothetical, it was simulated a power plant consuming the same quantity of bagasse, however, with the purchase of a medium pressure turbine, generating 2 MW surplus for sale. The third case considers the use of all the bagasse that is produced during the harvest in order to generate electric power. It is observed the acquisition of a high pressure cauldron and an extraction-condensation turbine. In this simulation, it is obtained 29 MW of electricity surplus. At last, the fourth case considers a high pressure cauldron, an extraction-condensation turbine and a counter pressure turbine in order to generate electric power, producing approximately 35, 2 MW surplus, facing the quantity of bagasse currently produced. However, in this simulation, only the bagasse from the harvest was used, remaining some quantity for sale after the harvest. Facing the facts, it is possible to implement a thermal power station, however, as noted, the existing risk is associated to the lack of policy capable to stimulate the sale of electric power via alternative sources of energy.